THE IMPORTANCE OF DEVELOPING SMALL AND MEDIUM-SIZED CITIES IN UZBEKISTAN (American Journal of Technology and Applied Sciences, 2024)
The article describes the socio-economic migration situation expected in Uzbekistan and the opportunities related to resources, which motivate the development of small and medium-sized cities, and the importance of controlling and scientifically managing this process.